The Role of Bim Technologies in the Information System of Education - Kokhorov Abdumonon Abdumutalibovich; Boltayeva Muhayyo Lutfillaevna (PT ANTIS International Publisher, 2024)
In the article of builders professional competence increase , modern informed from technologies wide use , formation of a specialist as a well-rounded, humane, comprehensively developed person and in them competence features research done.